The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1590/s0100-736x2012001200019
|View full text |Cite
|
Sign up to set email alerts
|

Strain and strain rate by two-dimensional speckle tracking echocardiography in a maned wolf

Abstract: Pesq. Vet. Bras. 32(12):1336-1340, dezembro 2012 1336 RESUMO.-[Strain e strain rate por meio de ecocardiograϐia speckle traking bidimensional em um lobo-guará.] A obtenção de parâmetros cardiovasculares em animais selvagens são importantes de serem avaliados, assim como em animais de companhia, para a obtenção da função miocárdica e determinação precoce de alterações cardíacas que poderiam evoluir para insuϐiciência cardíaca . A ecocardiograϐia speckle tracking (2D STE) é uma ferramenta nova que tem sido uti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
(30 reference statements)
2
3
0
Order By: Relevance
“…The E wave exhibited a mean velocity peak (89.6±1.43cm/s) greater than that of the A wave (74.9±1.22cm/s), and this pattern has also been reported for dogs of different breeds (Boon, 2011), minipigs (Lee et al, 2007 and maned wolves (Mantovani et al, 2012). These data allowed the evaluation of the diastolic function of the animals in this study as described for sedated minipigs (Lee et al, 2007) and maned wolves (Mantovani et al, 2012) that have been submitted to similar protocols (Lee et al, 2007). TDI has been demonstrated to be a sensitive technique for the quantitative evaluation of segmental myocardial movement (Wess et al, 2011) and is reproducible for examinations of basal cardiac function (D'Hooge et al, 2000)) in peccaries.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…The E wave exhibited a mean velocity peak (89.6±1.43cm/s) greater than that of the A wave (74.9±1.22cm/s), and this pattern has also been reported for dogs of different breeds (Boon, 2011), minipigs (Lee et al, 2007 and maned wolves (Mantovani et al, 2012). These data allowed the evaluation of the diastolic function of the animals in this study as described for sedated minipigs (Lee et al, 2007) and maned wolves (Mantovani et al, 2012) that have been submitted to similar protocols (Lee et al, 2007). TDI has been demonstrated to be a sensitive technique for the quantitative evaluation of segmental myocardial movement (Wess et al, 2011) and is reproducible for examinations of basal cardiac function (D'Hooge et al, 2000)) in peccaries.…”
Section: Discussionsupporting
confidence: 62%
“…The Doppler echocardiographic evaluation revealed a maximal aortic velocity (AVmax; 124.4±33.7cm/s) that was greater than the flow velocity in the pulmonary artery (Pmax; 78.2±2.3cm/s), as has been reported for domestic pigs (AVmax: 87±0.04; Pmax: 72±0.06) and minipigs (AVmax: 84±0.06; Pmax: 66±0.02cm/s) (Lee et al, 2007). The E wave exhibited a mean velocity peak (89.6±1.43cm/s) greater than that of the A wave (74.9±1.22cm/s), and this pattern has also been reported for dogs of different breeds (Boon, 2011), minipigs (Lee et al, 2007 and maned wolves (Mantovani et al, 2012). These data allowed the evaluation of the diastolic function of the animals in this study as described for sedated minipigs (Lee et al, 2007) and maned wolves (Mantovani et al, 2012) that have been submitted to similar protocols (Lee et al, 2007).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…The subjective analysis of segmental contractions did not note any complications related to the action of the anesthetic agents applied and noticed that the values for left ventricular fractional shortening (LVFS) by the Teicholz method and for the ejection fraction (EF) were maintained. The evaluation of a maned wolf (Chrysocyon brachyurus) under the same protocol (Mantovani et al 2012) presented similarities in the assessment of the systolic function in M-Mode, arterial ow, pulmonary ow and transmitral ow. The animal in question was described to weight 29 kg and, after adjusting the weight and the measurements obtained in the allometric scale (Cornell et al 2004), the values were similar to those observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…7 Although strain analysis by speckle tracking (2D-ST) is well established in veterinary medicine for companion animals, it remains scarce in the literature. 8 The Rhesus monkey is the most commonly used non-human primate in scientific research, despite the wide variety of species potentially available for preclinical studies. 9 Given the large population and availability of capuchin monkeys throughout Brazil, the present study acquired conventional echocardiographic measurements and evaluated myocardial function using the speckle tracking technique to verify the applicability of these animals as models for the study of cardiovascular alterations in humans.…”
Section: Introductionmentioning
confidence: 99%